A story of light : a short introduction to quantum field theory of quarks and leptons - Han, M. Y. (World Scientific, 2004)
This book presents the essential aspects of relativistic quantum fieldtheory, with minimal use of mathematics. It covers the development ofquantum field theory from the original quantization of electromagneticfield to the gauge field theory of interactions among quarks andleptons.